City of Neighborhoods : Memory, Folklore, and Ethnic Place in Boston - Buccitelli, Anthony Bak (Book collections on Project MUSE., 2016)
East Boston has long been known as an Italian neighborhood and Southie as an Irish one, while nearby North Quincy has seen in recent decades an influx of Chinese Americans and immigrants. Such urban spaces in America can become intimately intertwined with ethnic identities (Little Italy, Greektown, Chinatown, Little Havana). Yet local residents often readily acknowledge an underlying diversity-both historically and as a result of more recent changes-that complicates such stereotypes. Digging into the ever-shifting terrain of American ethnicity and urban spaces, Anthony Bak Buccitell.